2006
DOI: 10.1083/jcb.200510015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chromatin structure and mobility in living cells at sites of DNA double-strand breaks

Abstract: The repair of DNA double-strand breaks (DSBs) is facilitated by the phosphorylation of H2AX, which organizes DNA damage signaling and chromatin remodeling complexes in the vicinity of the lesion (Pilch, D.R., O.A. Sedelnikova, C. Redon, A. Celeste, A. Nussenzweig, and W.M. Bonner. 2003. Biochem. Cell Biol. 81:123–129; Morrison, A.J., and X. Shen. 2005. Cell Cycle. 4:568–571; van Attikum, H., and S.M. Gasser. 2005. Nat. Rev. Mol. Cell. Biol. 6:757–765). The disruption of DNA integrity induces an alteration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
452
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(504 citation statements)
references
References 60 publications
41
452
10
1
Order By: Relevance
“…These processes may be conserved, as broken DSB ends can exhibit limited or pronounced mobility in mammals [63][64][65][66] . Thus, it will be important to determine whether motor complexes contribute to DSB repair in different organisms including human.…”
Section: Discussionmentioning
confidence: 99%
“…These processes may be conserved, as broken DSB ends can exhibit limited or pronounced mobility in mammals [63][64][65][66] . Thus, it will be important to determine whether motor complexes contribute to DSB repair in different organisms including human.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNA damage checkpoint and repair proteins relocalize from a diffuse distribution to distinct subnuclear foci in a temporally regulated manner upon DNA damage, in both yeast and mammalian cells [31][32][33][34]. However, it is not clear if double-strand breaks (DSBs) are recruited to scaffolds for repair, or if repair factors assemble at sites of damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear if double-strand breaks (DSBs) are recruited to scaffolds for repair, or if repair factors assemble at sites of damage. Indeed, sites of damage arising from a targeted endonuclease [31] or γ-irradiation [32] are relatively immobile in the mammalian nucleus, suggesting that most DSB repair by non-homologous end joining, does not involve relocalization of damage to sites like PML-NBs. It remains possible, however, that specific pathways of DNA repair require specific nuclear subcompartments, since the efficiency of certain types of repair varies with the chromosomal context in which the damage occurs [35].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin relaxation in the vicinity of DSB has been observed in yeast 41 and mammalian cells. 42 Thus, it was shown that a local expansion of damaged chromatin occurs immediately after DSB, independently of ATM activation and H2AX phosphorylation but dependent on processes that hydrolyze ATP. 42 Moreover, it is speculated that local relaxation at the DSB site might also be a signal for ATM activation since chromatin decondensation induced by relaxing agents, such as chloroquine, and inhibitors of deacetylases can trigger ATM activation.…”
Section: Recognition and Signal Amplification Of Dna Damagementioning
confidence: 99%